Bentuk-Bentuk Interferensi Sintaksis Bahasa Indonesia Terhadap Bahasa Arab Pada Naskah Soal MFQ MTQ Nasional XXVI - Sihhatul Mahbubah; Muflihah (Universitas Yudharta Pasuruan, 2021)
Arabic is a foreign language that still survives its existence to this day. as a foreign language Arabic has the opportunity to be influenced by Indonesian as the first language. This interference is an inevitability but also should not be ignored. therefore, this research was conducted to describe forms of interference, especially in the realm of syntax. research object is a text about MFQ MTQ National XXVI. This research is descriptive qualitative and quantitative research. The main data of this research is the MFQ MTQ National XXVI. Data were collected by using the observation method and then analyzed using triangulation and descriptive-analytic techniques. The results showed that there were 10 forms of syntactic interference from Indonesian into Arabic from 130 questions of the MFQ MTQ National XXVI. This form of interference includes the interference of the concordance aspect, the interference of adjective-noun phrases (shifah-maushuf / na't-man'uut), the interference of sentences in the form of the number ismiyah (mubtada'-khabar), and the interference of the number noun phrases ('adad-ma' dud). Then after the interference data was presented, the result of the percentage level of interference in the MFQ MTQ National XXVI question text was 13%.